1998
DOI: 10.1086/311095
|View full text |Cite
|
Sign up to set email alerts
|

Initial On-Orbit Performance of NICMOS

Abstract: On 1997 February 13, Space Shuttle astronauts placed the Near-Infrared Camera and Multiobject Spectrometer (NICMOS) into the Hubble Space Telescope. Following installation, the servicing mission orbital verification program (SMOV) performed extensive testing of the instrument to verify that it can be operated and calibrated effectively. This program is essentially completed, and routine science observations have begun in most of the NICMOS modes of operation. This Letter describes the performance levels of NIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 4 publications
0
94
0
Order By: Relevance
“…Our object was examined by the HST on 1997 September 29 with the NIC2 camera of the NICMOS instrument (Thompson et al 1998). The observations were performed using fixed aperture and MULTIACCUM read-out mode with the filters F110W, F160W,F187N,F204M,and F212N (HST proposal 7228,PI: E. Young).…”
Section: Nic2/hstmentioning
confidence: 99%
“…Our object was examined by the HST on 1997 September 29 with the NIC2 camera of the NICMOS instrument (Thompson et al 1998). The observations were performed using fixed aperture and MULTIACCUM read-out mode with the filters F110W, F160W,F187N,F204M,and F212N (HST proposal 7228,PI: E. Young).…”
Section: Nic2/hstmentioning
confidence: 99%
“…Cotera et al (2001) observed HH 30 on 1997 September 29 with the NIC2 camera of the NICMOS instrument on HST (Thompson et al 1998). They obtained exposures in several filters, but here we consider only their 112 s exposure through the F204M filter (2.04 m, very roughly Johnson K ).…”
Section: Observationsmentioning
confidence: 99%
“…Repeated observations with UKIRT at both H and K-bands failed to detect any extended emission at the 4% level. High resolution observations with NICMOS on board the Hubble Space Telescope (Thompson et al 1997) also failed to detected any extended emission.…”
Section: Gl 989mentioning
confidence: 99%